Structural Insights into G Protein-Coupled Receptor Kinase Function - Homan, Kristoff T. (2013)
The atomic structure of a protein can greatly advance our understanding of molecular recognition and catalysis, properties of fundamental importance in signal transduction. However, a single structure is incapable of fully describing how a protein works, particularly when allostery is involved. Recent advances in the structure and function of G protein-coupled receptor (GPCR) kinases (GRKs) have concentrated on the mechanism of their inhibition by small and large molecules. These studies have generated a wealth of new information on the conformational flexibility of these enzymes, which opens new avenues for the development of selective chemical probes and provides deeper insights into the molecular basis for activation of these enzymes by GPCRs and phospholipids.